Blood Pressure and Mortality in the 4D Study - Babak Yazdani; Marcus E. Kleber; Graciela E. Delgado; Gökhan Yücel; Aruscha Asgari; Andreas L.H. Gerken; Clara Daschner; Niklas Ayasse; Winfried März; Christoph Wanner; Bernhard K. Krämer (Karger Publishers, 2023)
Introduction: Systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) are risk factors for cardiovascular mortality (CVM). Pulse pressure (PP) is an easily available parameter of vascular stiffness, but its impact on CVM in chronic dialysis patients with diabetes is unclear. Methods: Therefore, we have examined the predictive value of baseline, predialytic PP, SBP, DBP, and MAP in the German Diabetes and Dialysis (4D) study, a prospective, randomized, double-blind trial enrolling 1,255 patients with type 2 diabetes on hemodialysis in 178 German dialysis centers. Results: Mean age was 66.3 years, mean blood pressure 146/76 mm Hg, mean time suffering from diabetes 18.1 years, and mean time on maintenance dialysis 8.3 months. Considered as continuous variables, PP, MAP, SBP, and DBP could not provide a significant mortality prediction for either cardiovascular or all-cause mortality. After dividing the cohort into corresponding tertiles, we also did not detect any significant mortality prediction for PP, SBP, DBP, or MAP, both for all-cause mortality and CVM after adjusting for age and sex. Nevertheless, when comparing the HR plots of the corresponding blood pressure parameters, a pronounced U-curve was seen for PP for both all-cause mortality and CVM, with the trough range being 70-80 mm Hg. Discussion: In patients with end-stage renal disease and long-lasting diabetes mellitus predialytic blood pressure parameters at study entry are not predictive for mortality, presumably because there is a very high rate of competing mortality risk factors, resulting in overall very high rates of all-cause and CVM that may no longer be significantly modulated by blood pressure control.